A DESCRIPTIVE STUDY ON ENGLISH VOCABULARY TEACHING STRATEGY USING PICTURES FOR ELEMENTARY SCHOOL STUDENTS - Nur Indah; Samtidar Samtidar; Andi Muliati (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2023)
The purpose of this study is to describe the strategies used by teachers in restricting English vocabulary. In this study used a qualitative approach. The population used in this study were English teachers at Madania Makassar schools. Selection of the population is done by purposive sampling. Researchers conducted observations and interviews for data collection. From the results of data analysis and processing, it is known that the strategies used by English teachers at Madania Makassar schools to teach vocabulary are, Repeating the Words, Coloring the Picture, Grouping Words, Finding the Picture, Connecting Words and Pictures, and Name the Object Shown in the Picture. During the learning process, the teacher can manage the class well so that students are actively involved in learning. The books used during the learning process are books designed by the teacher, but still guided by the government's curriculum.. Keywords— Vocabulary, Teaching Strategies, Picture.